Penapisan Mikroba Laut Perombak Senyawa Nitril dan Protein yang Diisolasi Dari Spons di Perairan Ternate - Riffiani, Rini; Sulistinah, Nunik (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTScreening of Nitrile and Protein-Degrading Marine Bacteria Isolated from Sponge in TernateSea Water. Thirty three marine bacteria have been isolated from marine sponge in Ternate byenrichment culture. Screening bacteria-degrading nitrile was done by microtitter plate methodbased on growth ability tested by Iodonitrotetazolium chloride. Product of nitrile degradationwas determined by Gas Chromatography (GC) and the potential bacteria-degrading proteinwas also screened by using selected media which contained casein. The results showed thattwenty one isolates were able to show the clearing zone in selected media. Five isolatescapable of utilizing acetamide as the sole source of carbon and nitrogen. Acetate and ammoniaproduced for hydrolysis acetonitrile by using resting cell of Lysobacter sp.Key words: Nitrile, bacterium, sponge, Ternate